All-solid-state battery and manufacturing method thereof

By using metal oxides and metal protective layers and lithium alloying in all solid state batteries, the problem of uneven precipitation of lithium is solved, uniform deposition and reversible charging and discharge of lithium are achieved, and the life and durability of the battery are improved. Operate at room temperature.

CN119275360APending Publication Date: 2025-01-07HYUNDAI MOTOR CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311737807.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-06
Filing Date
2023-12-15
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The negative electrode material layer of all-solid state batteries has irreversible reactions due to the uneven precipitation of lithium, and has poor life and durability. Traditional methods such as metal powder coating cannot effectively solve the problem of uneven deposition of metal and lithium.

Method used

Using a protective layer including metal oxides and metals, by alloying with lithium, forming a lithium alloy and uniformly depositing lithium in the solid electrolyte layer, preventing the growth of lithium dendritic crystals, and using composite materials to increase the diffusion rate of lithium ions.

Benefits of technology

The uniform deposition of lithium and reversible charging and discharging are achieved, which improves the life and durability of the battery, can operate stably at room temperature, reduces the clamping pressure, and improves the battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275360A_ABST
    Figure CN119275360A_ABST
Patent Text Reader

Abstract

An all-solid-state battery and a method of manufacturing the same are disclosed. An all-solid-state battery includes a metal oxide and a metal that can be alloyed with lithium, thereby uniformly depositing lithium during charging and enabling operation at room temperature, e.g., 20-25 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an all-solid-state battery and a method for manufacturing the same, the all-solid-state battery including a metal oxide and a metal capable of alloying with lithium, thereby uniformly depositing lithium during charging and being capable of operating at room temperature. Background Art

[0002] The all-solid-state battery is configured to include a three-layer laminate having a positive electrode layer bonded to a positive electrode collector, a negative electrode active material layer bonded to a negative electrode collector, and a solid electrolyte layer provided between the positive electrode layer and the negative electrode active material layer.

[0003] The negative electrode active material layer of the all-solid-state battery can be formed by mixing the negative electrode active material with a solid electrolyte for obtaining ionic conductivity. Since the solid electrolyte has a higher specific gravity than the liquid electrolyte, the energy density of the conventional all-solid-state battery is lower than that of the lithium-ion battery. In this regard, research has been conducted on using lithium metal as a negative electrode to increase the energy density of the all-solid-state battery, but there are problems such as interface bonding, growth of lithium dendrites, price, and difficulty in forming a large area.

[0004] Recently, a storage-type negative electrode-free all-solid-state battery in which the negative electrode of the all-solid-state battery is removed and lithium is directly deposited on the negative electrode collector is being studied. However, the problem with the above-mentioned battery is that the irreversible reaction gradually increases due to the uneven precipitation of lithium, and the life and durability are very poor. In order to solve this problem, attempts have been made to coat the negative electrode collector with metal powder, but this produces unsatisfactory results, such as the phenomenon of uneven deposition of metal and lithium during charging, etc.

[0005] The statements in this section merely provide background information related to the present disclosure and may not constitute prior art. Summary of the invention

[0006] The present disclosure has been made in view of the problems encountered in the related art, and an object of the present disclosure is to provide an all-solid-state battery comprising a metal oxide and a metal capable of alloying with lithium, thereby uniformly depositing lithium during charging and being capable of operating at room temperature (e.g., 20-25°C).

[0007] Another object of the present disclosure is to provide a method for manufacturing an all-solid-state battery including metal oxides and metals.

[0008] The purpose of the present disclosure is not limited to the foregoing content. The purpose of the present disclosure can be clearly understood through the following description and achieved through the methods described in the claims and their combinations.

[0009] An embodiment of the present disclosure provides an all-solid-state battery, comprising a negative electrode collector, a protective layer disposed on the negative electrode collector, a solid electrolyte layer disposed on the protective layer, wherein the protective layer is located between the negative electrode collector and the solid electrolyte layer; a positive electrode layer, which is disposed on the solid electrolyte layer and comprises a positive electrode active material, wherein the solid electrolyte layer is located between the protective layer and the positive electrode layer; and a positive electrode collector, which is disposed on the positive electrode layer, wherein the positive electrode layer is located between the solid electrolyte layer and the positive electrode collector.

[0010] The protective layer may include a metal and a metal oxide, and the metal and the metal oxide are capable of alloying with lithium.

[0011] The metal may include silver (Ag), magnesium (Mg), zinc (Zn), gold (Au), or a combination thereof.

[0012] The metal oxide may include zinc oxide (Zn), tin oxide (Sn), silicon oxide (Si), germanium oxide (Ge), indium oxide (In), antimony oxide (Sb), bismuth oxide (Bi), gallium oxide (Ga), aluminum oxide (Al), titanium oxide (Ti), zirconium oxide (Zr), nickel oxide (Ni), iron oxide (Fe), cobalt oxide (Co), chromium oxide (Cr), magnesium oxide (Mg), or a combination thereof.

[0013] The mass ratio of metal oxide to metal in the protective layer may be in the range of 3:7 to 7:3.

[0014] Metal oxides can alloy with lithium at a higher voltage range than metals.

[0015] Metal oxides can alloy with lithium at voltages ranging from 0.4V to 0.7V, while metals can alloy with lithium at voltages ranging from 0.1V to 0.3V.

[0016] The lithium ion diffusion coefficient (D) of the protective layer can be between 1.2 and 2.3 m 2 / s range.

[0017] The metal oxide and the metal may have a particle size (D 50 ).

[0018] The thickness of the protective layer may be in the range of 1 μm to 20 μm.

[0019] Another embodiment of the present disclosure provides a method for manufacturing an all-solid-state battery, comprising: preparing a slurry by mixing metal oxides, metals, conductive materials and adhesives, forming a protective layer by applying the slurry to a negative electrode collector, forming a solid electrolyte layer on the protective layer, forming a positive electrode layer on the solid electrolyte layer, and forming a positive electrode collector on the positive electrode layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The above-mentioned and other features of the present disclosure are now described in detail with reference to certain exemplary embodiments of the present disclosure illustrated in the accompanying drawings, which are given hereinafter by way of illustration only and thus do not limit the present disclosure, and in which:

[0021] Figure 1 An embodiment of a cross-sectional view of an all-solid-state battery is shown;

[0022] Figure 2 Examples of metal oxides and metal alloying with lithium ions are shown;

[0023] Figure 3 An example of a scanning electron microscope (SEM) image showing a top view of a protective layer when a half-cell is charged;

[0024] Figure 4 An example of a SEM image showing a cross-sectional view of a charged half-cell;

[0025] Figure 5 shows the first discharge diagram of the half-cell according to the test example;

[0026] Figure 6 shows the 60th discharge graph of a half-cell according to a test example;

[0027] Figure 7 An image showing the results of evaluating the lifespan of a half-cell according to a test example;

[0028] Figure 8 The operation of the half-cell according to Comparative Example 1 is shown;

[0029] Fig. 9 The operation of the half-cell according to Comparative Example 2 is shown;

[0030] Fig.10 A diagram showing the results of evaluating the full battery life according to the test example;

[0031] Fig.11 shows the 1st and 100th discharge graphs of a full battery according to a test example;

[0032] Fig.12 A graph showing alloying of metal oxides and metals with lithium ions in different voltage ranges according to a test example;

[0033] Fig.13 An example of a half-cell potential diagram during a GITT (Galvanostatic Intermittent Titration Technique) pulse is shown;

[0034] Fig.14shows the analysis results of the XRD pattern of the full battery according to the test example;

[0035] Fig.15 An example of a SEM image of a cross section of a full cell during charge and discharge is shown;

[0036] FIG. 16A to FIG. 16C An example of an image showing oxygen (O) distribution near a protective layer during charge and discharge of a full cell; and

[0037] Figures 17A to 17C An example of an image showing the distribution of zinc (Zn) near a protective layer during charge and discharge of a full cell. DETAILED DESCRIPTION

[0038] The above and other objects, features and advantages of the present disclosure will be more clearly understood from the following embodiments in conjunction with the accompanying drawings. However, the present disclosure is not limited to the embodiments disclosed herein and may be modified into different forms. These embodiments are provided to thoroughly explain the present disclosure and fully convey the spirit of the present disclosure to those skilled in the art.

[0039] Throughout the accompanying drawings, the same reference numerals represent the same or similar elements. For clarity of the present disclosure, the size of the structure is depicted as being larger than its actual size. Although various elements may be described using terms such as "first", "second", etc., in this article, these elements are not limited by these terms. These terms are only used to distinguish one element from another element. For example, without departing from the scope of the present disclosure, the "first" element discussed below may be referred to as the "second" element. Similarly, the "second" element may also be referred to as the "first" element. As used herein, unless the context clearly indicates otherwise, the singular form is intended to also include the plural form.

[0040] When used in this specification, the terms "comprise", "include", "have", etc. specify the presence of the features, wholes, steps, operations, elements, components, or combinations thereof, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components, or combinations thereof. Moreover, when an element such as a layer, film, region, or sheet is referred to as being "on" another element, it can be directly on the other element, or there can be intermediate elements therebetween. Similarly, when an element such as a layer, film, region, or sheet is referred to as being "under" another element, it can be directly under the other element, or there can be intermediate elements therebetween.

[0041] Unless otherwise specified, all numerical values, values ​​and / or representations used in this article to represent the amount of components, reaction conditions, polymer compositions and mixtures should be considered as approximate values, including various uncertainties that affect measurement, which inherently occur in obtaining these values, etc., and therefore should be understood in all cases as modified by the term "about". In addition, when a numerical range is disclosed in this specification, the range is continuous and includes all values ​​from the minimum value of the range to its maximum value, unless otherwise specified. In addition, when such a range involves integer values, all integers from the minimum value to the maximum value are included unless otherwise specified.

[0042] In this specification, when a range is described for a variable, the variable includes all values ​​including the endpoints described in the range. For example, a range of "5 to 10" should be understood to include any sub-ranges, such as 6 to 10, 7 to 10, 6 to 9, 7 to 9, etc., as well as individual values ​​of 5, 6, 7, 8, 9 and 10, and should also be understood to include any values ​​between valid integers in the range, such as 5.5, 6.5, 7.5, 5.5 to 8.5, 6.5 to 9, etc. In addition, for example, a range of "10% to 30%" will be understood to include sub-ranges, such as 10% to 15%, 12% to 18%, 20% to 30%, etc., and all integers, including 10%, 11%, 12%, 13%, etc. up to 30%, and will also be understood to include any values ​​between valid integers in the range, such as 10.5%, 15.5%, 25.5%, etc.

[0043] Figure 1 2 is a cross-sectional view showing an all-solid-state battery. Referring to this, the all-solid-state battery may be configured such that the negative electrode collector 10, the protective layer 20, the solid electrolyte layer 30, the positive electrode layer 40, and the positive electrode collector 50 are sequentially stacked.

[0044] The all-solid-state battery can be an anode-free all-solid-state battery, in which, during charging, lithium metal, lithium alloy and lithium oxide (Li 2 O) is formed between the solid electrolyte layer and the negative electrode current collector.

[0045] The negative electrode current collector 10 may be a plate-shaped substrate having conductivity. The negative electrode current collector 10 may include nickel (Ni), stainless steel (SUS), or a combination thereof.

[0046] The negative electrode current collector 10 may be a high-density metal thin film having a porosity of less than 1%.

[0047] The negative electrode current collector 10 may have a thickness in the range of 1 μm to 20 μm, or in the range of 5 μm to 15 μm.

[0048] During charging of the all-solid-state battery, the protective layer 20 allows lithium ions (Li ions) to move from the positive electrode layer 40. + ) is uniformly deposited between the solid electrolyte layer 30 and the negative electrode collector 10. Also, the protective layer 20 prevents an internal short circuit from occurring due to the growth of lithium dendrites. A detailed description thereof is provided in more detail below.

[0049] The protective layer 20 may include metals and metal oxides. The metals and metal oxides may form alloys with lithium alone.

[0050] The metal may include silver (Ag), magnesium (Mg), zinc (Zn), gold (Au), or a combination thereof.

[0051] The metal oxide may include zinc oxide (Zn), tin oxide (Sn), silicon oxide (Si), germanium oxide (Ge), indium oxide (In), antimony oxide (Sb), bismuth oxide (Bi), gallium oxide (Ga), aluminum oxide (Al), titanium oxide (Ti), zirconium oxide (Zr), nickel oxide (Ni), iron oxide (Fe), cobalt oxide (Co), chromium oxide (Cr), magnesium oxide (Mg), or a combination thereof.

[0052] In certain embodiments, the metal oxide includes zinc oxide (ZnO).

[0053] The lithium ions moving from the positive electrode layer 40 flow into the solid electrolyte layer 30. Figure 1 When the metal oxide included in the protective layer 20 is zinc oxide, the metal oxide undergoes an electrochemical reaction with lithium ions as shown in Schemes 1 and 2 below.

[0054] 2ZnO+4Li + →2Zn + +2Li 2 O(Solution 1)

[0055] Zn+Li + →Zn-Li (alloy) (Scheme 2)

[0056] Specifically, the metal oxide and lithium ions react according to Scheme 1 to produce lithium oxide (Li 2 O) and zinc (Zn), and zinc (Zn) reacts with other lithium ions to form a lithium zinc alloy (Zn—Li).

[0057] Furthermore, the lithium ions moving from the positive electrode layer 40 to the protective layer 20 undergo an electrochemical reaction with the metal as shown in Scheme 3 below.

[0058] Ag+Li + →Ag-Li (alloy) (Scheme 3)

[0059] Specifically, the metal and lithium ions react according to Scheme 3 to form a lithium-silver alloy (Ag—Li).

[0060] exist Figure 2 The formation of lithium zinc alloy (Zn-Li) and lithium silver alloy (Ag-Li) is shown in FIG.

[0061] The lithium alloy not only stores lithium ions but also serves as a seed so that the lithium ions can be deposited as lithium metal.

[0062] Here, lithium oxide (Li 2 O) inhibits the growth of lithium dendrites and prevents metal oxide aggregation. Specifically, lithium oxide (Li 2 O) not only serves as a protective film, but also allows the uniform deposition of lithium metal and lithium alloys so that reversible charging and discharging can occur.

[0063] Therefore, the protection layer 20 may include lithium metal, lithium oxide, and two types of lithium alloys during charging.

[0064] When the all-solid-state battery is discharged, the opposing reactions of Scheme 1, Scheme 2, and Scheme 3 occur, enabling reversible charging and discharging.

[0065] The metal oxide and the metal may have a particle size (D 50 If the particle size of metal oxide and metal (D 50 ) is 1 μm or more, the particle size of the lithium alloy and lithium oxide formed of the metal oxide and the metal may increase excessively, making it difficult to obtain the above-mentioned effect.

[0066] The protective layer 20 may further include an adhesive that imparts adhesion between the metal oxide and the metal. The adhesive may include any material widely used in the technical field to which the present disclosure belongs, and may include, for example, butadiene rubber (BR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), polyethylene oxide (PEO), or a combination thereof.

[0067] The mass ratio of the metal oxide to the metal in the protective layer 20 may be in the range of 3:7 to 7:3. If the mass ratio of the metal oxide to the metal is less than 3:7 and thus the amount of the metal oxide is small, or if the mass ratio thereof exceeds 7:3 and thus the amount of the metal oxide is large, reversible charging and discharging may become difficult due to uneven deposition of the lithium alloy because the metal oxide forms an alloy with lithium in a higher voltage range than the metal.

[0068] The protective layer 20 does not include a separate carbon material. Conventional negative electrode-free all-solid-state batteries use carbon materials and the like to provide a space where lithium can be precipitated or deposited. However, in the present disclosure, since lithium ions are precipitated or deposited in the form of lithium alloys formed by the reaction of metal elements derived from metal oxides with lithium ions, lithium alloys formed by the reaction of metals with lithium ions, and lithium metals grown therefrom, charging and discharging can be performed reversibly without using a separate carbon material.

[0069] The protective layer 20 may have a thickness in the range of 1 μm to 20 μm. If the thickness of the protective layer 20 is less than 1 μm, the above effects cannot be obtained due to insufficient amount of metal oxide, and if the thickness of the protective layer exceeds 20 μm, reversible charging and discharging may become difficult due to excessive thickness.

[0070] The lithium ion diffusion coefficient (D) of the protective layer can be between 1.2 and 2.3 m 2 / s range.

[0071] The solid electrolyte layer 30 may be interposed between the positive electrode layer 40 and the negative electrode current collector 10 to allow lithium ions to move between the two members.

[0072] The solid electrolyte layer 30 may include an oxide-based solid electrolyte or a sulfide-based solid electrolyte. Here, a sulfide-based solid electrolyte having high lithium ion conductivity may be used. The sulfide-based solid electrolyte is not particularly limited, and examples thereof may include one or more of the following: Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -LiBr, Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2S-SiS 2 -LiCl, Li 2 S-SiS 2 -B2S3-LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are positive numbers, and Z is any one selected from Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (wherein x and y are positive numbers, and M is any one selected from P, Si, Ge, B, Al, Ga and In), Li 10 G 2 S 12 wait.

[0073] The positive electrode layer 40 may include a positive electrode active material, a solid electrolyte, a conductive material, a binder, and the like.

[0074] The positive electrode active material may be an oxide active material or a sulfide active material.

[0075] Examples of oxide active materials may include: rock salt layer type active materials, such as LiCoO 2 , LiMnO 2 , LiNiO 2 , LiVO 2 , Li 1+x Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 One or more of: spinel active materials, such as LiMn 2 O 4 , Li(Ni 0.5 Mn 1.5 ) 4 etc.; Inverse spinel active materials, such as LiNiVO 4 , LiCoVO 4etc.; Olivine-type active materials, such as LiFePO 4 , LiMnPO 4 , LiCoPO 4 , LiNiPO 4 etc.; Silicon-containing active materials, such as Li 2 FeSiO 4 , Li 2 MnSiO 4 etc.; rock salt layer type active materials in which part of the transition metal is replaced by different metals, such as LiNi 0.8 Co (0.2-x) Al x O 2 (0<x<0.2); spinel-type active materials in which a portion of the transition metal is replaced by a different metal, such as Li 1+x Mn 2-x-y M y O 4 (wherein M is at least one selected from Al, Mg, Co, Fe, Ni and Zn, 0<x+y<2); lithium titanate such as Li 4 Ti 5 O 12 ,wait.

[0076] Examples of sulfide active materials may include one or more of copper Chevrel, iron sulfide, cobalt sulfide, nickel sulfide, and the like.

[0077] The solid electrolyte may be an oxide solid electrolyte or a sulfide solid electrolyte. Here, a sulfide-based solid electrolyte having high lithium ion conductivity may be used. The sulfide-based solid electrolyte is not particularly limited, and embodiments thereof may include one or more of the following: Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -LiBr, Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 S-SiS2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B2S3-LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are positive numbers, and Z is any one selected from Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (wherein x and y are positive numbers, and M is any one selected from P, Si, Ge, B, Al, Ga and In), Li 10 G 2 S 12 wait.

[0078] Examples of the conductive material may include one or more of carbon black, conductive graphite, ethylene black, graphene, and the like.

[0079] Embodiments of the adhesive may include one or more of butadiene rubber (BR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), polyethylene oxide (PEO), and the like.

[0080] The positive electrode current collector 50 may be a plate-shaped substrate having conductivity. The positive electrode current collector 22 may include aluminum foil.

[0081] A method for manufacturing an all-solid-state battery may include preparing a slurry by mixing metal oxides, metals, conductive materials and binders, forming a protective layer by applying the slurry to a negative electrode collector, forming a solid electrolyte layer on the protective layer, forming a positive electrode layer on the solid electrolyte layer, and forming a positive electrode collector on the positive electrode layer.

[0082] Here, the metal oxide, the metal, the conductive material, and the binder are as described above, and thus a detailed description thereof is omitted.

[0083] The slurry can be prepared by adding the metal oxide, etc. to a solvent and mixing. The solvent is not particularly limited, and any solvent capable of dispersing the metal oxide, etc. can be used. For example, the solvent may include N-methylpyrrolidone (NMP), water, ethanol, isopropanol, or a combination thereof.

[0084] The slurry may have a solid content in the range of 1 wt.% to 20 wt.%. When the solid content thereof falls within the above range, a protective layer may be more easily formed.

[0085] The solid electrolyte layer may be formed using a slurry including a solid electrolyte or by pressing a solid electrolyte in powder form. Also, the positive electrode layer may be formed using a slurry including a positive electrode active material or by pressing a positive electrode active material in powder form.

[0086] The forming of the protective layer, the forming of the solid electrolyte layer, and the forming of the positive electrode layer are not mentioned in a chronological order, and the individual components may be formed simultaneously or at different times. The method may include not only forming the solid electrolyte layer directly on the protective layer and forming the positive electrode layer directly on the solid electrolyte layer, but also manufacturing the individual components separately and then stacking them. Figure 1 In the structure shown.

[0087] The metal and metal oxide in the method for manufacturing an all-solid-state battery may include contents that substantially overlap with those of the all-solid-state battery described above, and thus a redundant description thereof is omitted.

[0088] A better understanding of the present disclosure can be obtained through the following examples. However, these examples are only set forth to illustrate the present disclosure and should not be construed as limiting the scope of the present disclosure.

[0089] Example 1

[0090] Stainless steel (SUS) was used as a negative electrode collector, and slurry was prepared by adding zinc oxide (ZnO) as a metal oxide, silver (Ag) as a metal, and PVDF as a binder to NMP as a solvent, and the slurry was coated on the negative electrode collector to form a protective layer. A half-cell was manufactured by sequentially stacking lithium metal, a solid electrolyte layer, and a negative electrode collector having a protective layer formed thereon.

[0091] Example 2

[0092] The slurry prepared in the same manner as in Example 1 was applied to stainless steel to form a protective layer, and NCM 711 (loading: 25 mg / cm 2 ) forms a positive electrode. A full battery is manufactured by sequentially stacking a positive electrode, a solid electrolyte layer, and a negative electrode current collector having a protective layer formed thereon.

[0093] Comparative Example 1

[0094] A half-cell was manufactured in the same manner as in Example 1, except that the slurry was prepared by adding only zinc oxide (ZnO), which is a metal oxide, to NMP as a solvent. Figure 3 A top view of the protective layer is shown in Figure 4 A cross-sectional view of the fabricated half-cell is shown in FIG.

[0095] Comparative Example 2

[0096] A half cell was manufactured in the same manner as in Example 1, except that a slurry was prepared by adding only silver (Ag), which is a metal, to NMP as a solvent.

[0097] Comparative Example 3

[0098] A full cell was manufactured in the same manner as in Example 2 using the slurry of Comparative Example 1.

[0099] Comparative Example 4

[0100] A full cell was manufactured in the same manner as in Example 2 using the slurry of Comparative Example 2.

[0101] Test Example 1

[0102] At about 25°C at 1 mA / cm 2 The current density is 3.5 mAh / cm 2 The half-cell according to Example 1 was charged and discharged under conditions of a deposition capacity of 1.5 Å.

[0103] Figure 5 shows the first charge / discharge diagram of the half-cell according to Example 1, and Figure 6 The 60th charge / discharge graph of the half-cell according to Example 1 is shown. Figure 5 and Figure 6 , zinc oxide (ZnO) and silver (Ag) and lithium ions (Li + ) electrochemical reaction, and the half-cell operates stably.

[0104] Figure 7Shown are the results of evaluating the life of the half-cell according to Example 1. The half-cell had an initial efficiency of 80% and an average coulombic efficiency (%) of about 99% or more during 60 cycles.

[0105] Figure 8 The operation of the half-cell according to Comparative Example 1 is shown, and Fig. 9 The operation of the half-cell according to Comparative Example 2 is shown. Figure 8 and Fig. 9 , when the protective layer 20 includes only zinc oxide (ZnO) or only silver (Ag), the battery cannot operate normally.

[0106] Test Example 2

[0107] Fig.10 is a graph showing the results of evaluating the life of the full battery according to Example 2, and Fig.11 The 1st and 100th discharge graphs of a full cell according to Example 2 are shown. The full cell was charged and discharged at about 25° C. under 0.2C (C rate) conditions. Fig.10 and Fig.11 , the capacity of the first cycle of the full battery is 150 mAh / g, and compared with the first cycle, the capacity retention rate after 50 cycles is 79.4%, and the capacity retention rate after 100 cycles is 73.5%.

[0108] Fig.12 is a graph showing alloying of metal oxides and metals with lithium in different voltage ranges. In this regard, zinc oxide (ZnO) forms an alloy with lithium at 0.4V to 0.7V, and silver (Ag) forms an alloy with lithium at 0.1V to 0.3V, confirming the reaction with lithium in different voltage ranges.

[0109] also, Fig.13 The half-cell potential diagram during a GITT (galvanostatic intermittent titration technique) pulse is schematically shown (A. Nickol et al. Electrochemical Society, 167(9), 090546(2020)). Fig.13 In FIG. 5 , the lower graph shows a current pulse applied for a short time, and the upper graph shows the time-voltage profile corresponding to the current pulse. According to the voltage rise (E 0 →E 1 →E 2 ) and the IR drop of the voltage in the remaining stages (E 2 →E 3 →E 4 ), the lithium ion diffusion coefficient (D) can be calculated using the following equation 1, and from Fig.12The results of calculating the lithium ion diffusion coefficient are shown in Table 1 below.

[0110]

[0111] Here, r P represents the average particle size of the active material in the reference electrode (original), and t P Indicates the pulse duration.

[0112] Table 1

[0113] Example 2 Comparative Example 3 Comparative Example 4 Reference electrode (second pulse) 0.209842 0.05684 0.040717 Zinc oxide lithiation zone 0.022919 0.020467 - Silver lithiation area 1.474478 - 1.128904

[0114] Reference Fig.12 As shown in Table 1, the D value of Example 2 is higher than those of Comparative Examples 3 and 4, and zinc oxide (ZnO) and silver (Ag) are lithiated in sequence.

[0115] In addition, in Example 2, Comparative Example 3 and Comparative Example 4 before lithiation, the D value of Example 2 is the largest, and in the zinc oxide (ZnO) lithiation region and the silver (Ag) lithiation region, the D value of Example 2 is greater than the D value of Comparative Example 3 or Comparative Example 4, confirming that the lithium ion diffusion rate is high when the composite material is used compared to when a single material is used. Specifically, when a battery including an electrode formed of a composite material including zinc oxide and silver is used, lithium ions are easily diffused, while solving the problem that a battery including an electrode formed of a single material including zinc oxide or silver cannot operate.

[0116] Therefore, when an electrode formed of the composite material is used, uniform lithium deposition may be induced in different voltage ranges, and the load of zinc oxide (ZnO) and silver (Ag) may be dispersed or reduced, enabling more stable lithium deposition.

[0117] Fig.14 The analysis result of the XRD pattern of the full battery according to Example 2 is shown. Referring to this, when lithium is deposited on the protective layer, LiZn alloy and Li are formed. In addition, reversible charging and discharging can be performed.

[0118] Fig.15 SEM images of a full battery according to Example 2 before charging (a), after charging (b), and during discharge (c) are shown, with the passage of time during charging and discharging. FIG. 16A to FIG. 16C shows the oxygen (O) distribution, and FIG. 17A to FIG. 17C Zinc (Zn) distribution is shown.

[0119] Reference Fig.15 , FIG. 16A to FIG. 16C and FIG. 17A to FIG. 17C, before charging, oxygen (O) and zinc (Zn) were distributed over a wide area in the protective layer in the reference electrode, and during charging, lithium was uniformly deposited in the protective layer and at the interface between the negative electrode current collector 10 and the protective layer 20. During discharge, oxygen (O) and zinc (Zn) returned to the same distribution as before charging, confirming that the all-solid-state battery can be reversibly charged and discharged while minimizing dead lithium.

[0120] As is apparent from the above description, the all-solid-state battery enables lithium to be uniformly deposited on the protective layer through the metal oxide and the metal, and its stable operation is possible even at room temperature (e.g., 20-25° C.), so that the clamping pressure applied to the all-solid-state battery can be reduced. Therefore, the all-solid-state battery with improved performance and durability can be operated at room temperature in an actual EV.

[0121] The effects of the present disclosure are not limited to the above-mentioned effects. It should be understood that the effects of the present disclosure include all effects that can be inferred from the description of the present disclosure.

Claims

1. An all-solid-state battery, comprising: A negative electrode current collector; A protective layer, disposed on the negative electrode current collector; A solid electrolyte layer is disposed on the protective layer; a positive electrode layer disposed on the solid electrolyte layer and including a positive electrode active material; and a positive electrode current collector, disposed on the positive electrode layer, Wherein, the protective layer comprises metal and metal oxide, and The metal and the metal oxide are capable of alloying with lithium.

2. The all-solid-state battery according to claim 1, wherein: The metal includes silver (Ag), magnesium (Mg), zinc (Zn), gold (Au), or a combination thereof.

3. The all-solid-state battery according to claim 1, wherein: The metal oxide includes zinc oxide (Zn), tin oxide (Sn), silicon oxide (Si), germanium oxide (Ge), indium oxide (In), antimony oxide (Sb), bismuth oxide (Bi), gallium oxide (Ga), aluminum oxide (Al), titanium oxide (Ti), zirconium oxide (Zr), nickel oxide (Ni), iron oxide (Fe), cobalt oxide (Co), chromium oxide (Cr), magnesium oxide (Mg) or a combination thereof.

4. The all-solid-state battery according to claim 1, wherein: The mass ratio of the metal oxide to the metal in the protective layer is 3:7 to 7:

3.

5. The all-solid-state battery according to claim 1, wherein: The metal oxide is configured to form an alloy with lithium in a higher voltage range than the metal.

6. The all-solid-state battery according to claim 1, wherein: The metal oxide is configured to form an alloy with lithium at a voltage in a range of 0.4 V to 0.7 V, and Wherein the metal is configured to form an alloy with lithium at a voltage in the range of 0.1V to 0.3V.

7. The all-solid-state battery according to claim 1, wherein: The protective layer has a thickness of 1.2 m 2 / s to 2.3m 2 / s range of lithium ion diffusion coefficient (D).

8. The all-solid-state battery according to claim 1, wherein: The metal oxide and the metal have a particle size (D 50 ).

9. The all-solid-state battery according to claim 1, wherein: The protective layer has a thickness in the range of 1 μm to 20 μm.

10. A method for manufacturing an all-solid-state battery, the method comprising: preparing a slurry by mixing a metal oxide, a metal, a conductive material, and a binder; forming a protective layer by applying the slurry to the negative electrode current collector; forming a solid electrolyte layer on the protective layer; forming a positive electrode layer on the solid electrolyte layer; as well as A positive electrode current collector is formed on the positive electrode layer.

11. The method according to claim 10, wherein: The metal includes silver (Ag), magnesium (Mg), zinc (Zn), gold (Au), or a combination thereof.

12. The method according to claim 10, wherein: The metal oxide includes zinc oxide (Zn), tin oxide (Sn), silicon oxide (Si), germanium oxide (Ge), indium oxide (In), antimony oxide (Sb), bismuth oxide (Bi), gallium oxide (Ga), aluminum oxide (Al), titanium oxide (Ti), zirconium oxide (Zr), nickel oxide (Ni), iron oxide (Fe), cobalt oxide (Co), chromium oxide (Cr), magnesium oxide (Mg) or a combination thereof.

13. The method according to claim 10, wherein: The mass ratio of metal oxide to metal in the protective layer is 3:7 to 7:

3.

14. The method according to claim 10, wherein: The protective layer has a thickness of 1.2 m 2 / s to 2.3m 2 / s range of lithium ion diffusion coefficient (D).

15. The method according to claim 10, wherein: The metal oxide and the metal have a particle size (D 50 ).

16. The method according to claim 10, wherein: The protective layer has a thickness in the range of 1 μm to 20 μm.